Albania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
Inflation in Southeastern European (SEE) countries has been comparable with euro area inflation, partly owing to on the one hand, high initial price levels. On the other hand, the exchange rate regime is of paramount importance, including the inflation-targeting regime pursued in Albania. The analysis also explores additional heterogeneity between SEE and other regions. Two fiscal rules-a debt rule and an expenditure rule with a debt brake-are discussed in the context of Albania's current economic outlook. Both rules will contribute toward enhancing fiscal sustainability in Albania.